Soft Adventure and Spiritual Tourism: A Case Study of Khaptad National Park - Badal, Bharat Prasad (Janabhawana Research Journal, 2024)
Tourism for lifetime pride is adventure tourism. Khaptad National Park and its core area are the land of meditation of renounced (sage) Yogi Khaptad Baba. It is a natural beauty hub and centre of soft adventure tourism in Far West Nepal. The land is adventurous from different dimensions of tourism. Thus, to find out the elements of adventure tourism in the Khaptad area the study has been conducted. To explore the elements, the study has analyzed the attraction component of adventure tourism in the zone. It is a case study of Khaptad National Park, Nepal. The facts were collected through field observation, focus group discussion, and qualitative interviews on qualitative exploratory approach. From the review, discussion, and analysis, it was found that the land is perfectly suitable for high-altitude hiking, trekking, bird and butterfly watching, rock climbing, yoga, meditation, and snow sports. Any type of outdoor sports (Cricket, football, mountain biking, running, skiing, and many more) at cool high altitudes can be organized in the Khaptad. The land can be the milestone for Nepalese soft adventure sports tourism including spiritual, cultural, and eco-tourism. However, infrastructure tourism development in the pristine land must be as much as environmentally friendly. One ring road around the Khaptad National Park is advisable but motorable roads should be constructed upward to the plateau. It is the land like a natural heaven that must not be indulged by concretization and modernization.